The Effects of Soft Contact Lens Wear on Corneal Thickness, Curvature, and Surface Regularity - Sah, RP; Paudel, N; Chaudhary, M; Adhikari, P; Mishra, SK (Journal of Chitwan Medical College, 2014)
Contact lenses have various cosmetic and optical advantages over spectacles. However, long term lens use might affect the normal corneal anatomy and physiology in a variety of ways. The aim of this study was to determine the effect of soft contact lens wear on corneal thickness, curvature, and surface regularity.A total of 138 eyes of 69 subjects wearing contact lenses for more than 1 year were evaluated. One eye of each case was randomly selected for the analysis. Nidek Magellan Mapper corneal topography system was used to evaluate the anterior corneal topography. Central corneal thickness (CCT) was measured using Quantel Medical Axis II PR. Corneal topography and CCT measurements on 138 eyes of 69 subjects were performed. The mean age of the cases and controls was 24.76 ± 5.52 25.13±5.49 years respectively. The mean duration of contact lens wear was 4.83±4.19 years. The mean CCT in case and control group was 527.56±37.40 microns and 544.60±26.10 microns respectively. The mean central corneal thickness in the cases was significantly less by about 16.31 μm in comparison to controls (P <0.05, 95% CI of the difference: 9 μm - 24μm). The SRI and SAI indices were significantly greater in contact lens wearers than in the control group (P = 0.00 for both SRI and SAI).Regular corneal pachymetry and topography assessments are mandatory in soft contact lens users as long term lens wear appears to reduce the central corneal thickness and increase the corneal surface irregularity. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10861 Journal of Chitwan Medical College 2014; 4(2): 35-39